2015
DOI: 10.1590/1678-457x.6815
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the HS-SPME-GC/MS technique for determining volatile compounds in red wines made from Isabel grapes (Vitis labrusca)

Abstract: Brazilian wine production is characterized by Vitis labrusca grape varieties, especially the economically important Isabel cultivar, with over 80% of its production destined for table wine production. The objective of this study was to optimize and validate the conditions for extracting volatile compounds from wine with the solid-phase microextraction technique, using the response surface method. Based on the response surface analysis, it can be concluded that the central point values maximize the process of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…The results showed that DVB/CAR/PDMS had the highest extraction efficiency, followed by PDMS and PA. Arcanjo et al. (2015) also found PDMS/CAR/DVB exhibited higher performance than the CAR/PDMS. These results may be due to the feature of DVB/CAR/PDMS fiber, which increased the retention capacity of VOCs by increasing both adsorption and distribution to the stationary phase (Wong et al., 2009).…”
Section: Resultsmentioning
confidence: 92%
“…The results showed that DVB/CAR/PDMS had the highest extraction efficiency, followed by PDMS and PA. Arcanjo et al. (2015) also found PDMS/CAR/DVB exhibited higher performance than the CAR/PDMS. These results may be due to the feature of DVB/CAR/PDMS fiber, which increased the retention capacity of VOCs by increasing both adsorption and distribution to the stationary phase (Wong et al., 2009).…”
Section: Resultsmentioning
confidence: 92%
“…Another alcohol, 1-hexanol, was only detected in the SB wine and is associated with a wine's herbal aroma (Rocha et al, 2004). On the QM and MR wines, linalool was detected, which contributes to the floral aroma (Jiang et al, 2013). Ot is of note that this volatile varied significantly among the analyzed samples, suggesting that although the wines were produced with the same cultivars, other production factors, such as the time of grape harvesting and the technological processes used, might influence the aroma of the final product.…”
Section: Estersmentioning
confidence: 99%
“…These compounds contribute to a wine's fruity aroma and result from the reaction of acetyl coenzyme A (acetyl-CoA) with higher alcohols generated from amino acid or carbohydrate degradation (Welke et al, 2012). Esters are associated with fruity descriptors: butyric acid, 2-methylbutyl ester and ethyl hexanoate with apple aroma, propanoic acid, dimethyl ester and ethyl butyrate with pineapple aroma, and ethyl succinate with apple and strawberry aromas (Jiang et al, 2013). Tao et al (2008) detected isoamyl acetate, isoamyl lactate and octanoate acetate in red wine made from vinifera cultivars and found aroma notes related to banana, raspberry and fruity aroma, respectively, and these compounds had a positive contribution to wine quality.…”
Section: Estersmentioning
confidence: 99%
“…Once the variability ranges have been established for the factors, optimization based on multivariate statistics can be achieved through two fundamental approaches related to the DoE: two-level factorial designs and response surface methodologies (RSM) [28][29][30] with the latter including, among others, central composite (CCD) [25,31], Doehlert matrix (DM) [32,33], three-level factorial (3K) and Box Behnken (BBD) designs [27].…”
Section: Optimization Of Hs-spme Parameters With Multivariate Statistical Analysismentioning
confidence: 99%
“…This is the aspect that most differentiates RSM approaches actually reported in the literature for the optimization of the extraction conditions for wine volatile compounds. Arcanjo et al [31] reported the application of RSM based on a rotatable central composite design (RCCD) to improve the conditions for extracting volatiles from Isabel wine. In this work, the RCCD was used to evaluate the effects of three independent parameters: temperature, equilibration and extraction time on three different responses, namely, the total number of peaks detected upon a chromatographic separation, the total area under the detected peaks and the area of the peak of isoamyl acetate, a typical volatile compound present in wine headspace, to define the best conditions for a high extractability of volatiles.…”
Section: Optimization Of Hs-spme Parameters With Multivariate Statistical Analysismentioning
confidence: 99%